TINGKAT PEMAHAMAN MAHASISWA TERHADAP UPACARA ADAT NAIK DANGO MASYARAKAT DAYAK KANAYANT - Sadewo, Yosua Damas Sadewo; Pebria Dheni Purnasari; Sabinus Beni (JURNAL BORNEO AKCAYA, 2020)
The purpose of this study is to describe the understanding of STIM Shanti Bhuana students on Naik Dango Traditional Ceremony. This study applied a qualitative descriptive method. The result showed that the students understood Naik Dango well. Their understanding was perceived from the 3 indicators. They were the meaning of Naik Dango; the implementation of Naik Dango; and the functions of Naik Dango. Most respondents were aware that this traditional ceremony was an expression of gratitudes for the rice harvest to God. Besides, the implementation of Naik Dango Traditional Ceremony was an event to show the development various traditional arts. This event was not only an expression of gratitudes to God but also an attempt to strengthen the relationship among the communities. Keywords: Level of Understanding, Traditional Ceremonies, Naik Dango, Dayak Kanayant